Shakespeare the basics - McEvoy, Sean 1959- (Oxon, [England] Routledge, 2006)
"The way in which Shakespeare's plays are studied has undergone considerable change in recent years. The new edition of this guide, aimed squarely at the student new to Shakespeare, is based on the exciting novel approaches shaping Shakespeare studies. This volume provides a thorough general introduction to the plays." "Sean McEvoy illustrates how interpretations of Shakespeare are linked to cultural and political contexts and provides readings of the most frequently studied plays in the light of contemporary critical thought. Now fully updated to include discussion of criticism and performance in the last five years, a new chapter on Shakespeare on film, and a broader critical approach, this book is the essential resource for all students of Shakespeare."--Jacket
Shakespeare's language (1) -- Shakespeare's language (2) -- Types of stage action -- The plays in performance -- Shakespeare on film -- What is genre? -- Understanding comedy: The taming of the shrew, A midsummer night's dream, Measure for measure, The merchant of Venice and Twelfth night -- Understanding history: King Richard II, King Henry IV part I and King Henry V -- Understanding tragedy: Hamlet, King Lear, Macbeth and Othello -- Understanding romance: The winter's tale and The tempest.
Includes bibliographical references (pages [272]-282) and index.
Keywords: Shakespeare, William -- 1564-1616 -- Outlines, syllabi, etc